2015
DOI: 10.19070/2332-290x-si02001
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelial Cell Line Suppression of Phagolysosome Activation

Abstract: The eye is an immune privileged tissue with multiple mechanisms of immunosuppression to protect the light gathering tissues from the damage of inflammation. One of theses mechanisms involves retinal pigment epithelial cell suppression of phagosome activation in macrophages. The objective of this work is to determine if the human RPE cell line ARPE-19 is capable of suppressing the activation of the phagolysosome in macrophages in a manner similar to primary RPE. The conditioned media of RPE eyecups, sub-conflue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Most of these studies looked at the uptake and not necessarily the phagosome maturation pathway. The results in this manuscript with our previous publication showing suppression of the phagolysosome activation (5, 6, 22) demonstrates that it is not the uptake but the maturation of the phagocytic pathway that is regulated by α-MSH and NPY.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Most of these studies looked at the uptake and not necessarily the phagosome maturation pathway. The results in this manuscript with our previous publication showing suppression of the phagolysosome activation (5, 6, 22) demonstrates that it is not the uptake but the maturation of the phagocytic pathway that is regulated by α-MSH and NPY.…”
Section: Discussionsupporting
confidence: 63%
“…In addition, microglial cells in the healthy neuroretina have similar alternatively activated myeloid cell characteristics (3). In eyes with wounded RPE, the RPE do not mediate the alternative activation but promote macrophage/microglial cell differentiation into proinflammatory M1 or wound repairing/anti-inflammatory M2 cells (3, 5). The wounded RPE monolayer continues to produce NPY and is greatly diminished in α-MSH production (3).…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytizing materials is central for an APC to process antigen for presentation on MHC class II molecules (104). Recently we have found that the process of phagocytosis is also altered by the RPE through its release of a-MSH and NPY (105,106). The neuropeptides mediate a differential regulation of phagocytic uptake of gram-negative and gram-positive bacteria (107).…”
Section: Rpe and Regulation Of Immunity Rpe Influenced Activity Of Macrophagesmentioning
confidence: 99%
“…The RPE from eyes with autoimmune uveitis do not suppress the phagocytic pathway, and this may be associated with high levels of IL-6 expression (105). The regulation of phagolysosome activation is dependent also on the RPE maintaining an intact monolayer (106). Therefore, one potential contribution of the RPE to immune privilege is its suppression of the processing and presentation of self-antigens by retinal APC that would prevent the activation of autoimmune disease-mediating effector T cells.…”
Section: Rpe and Regulation Of Immunity Rpe Influenced Activity Of Macrophagesmentioning
confidence: 99%
“…Treatment of human corneal buttons for transplantation retains epithelial cells with less cell death [16]. The neuropeptide prevents apoptosis in cultured macrophages and RPE cells [17,55]. In addition, the effects of augmenting the melanocortin pathways may be associated with which melanocortin receptor (MCr) is stimulated.…”
Section: Discussionmentioning
confidence: 99%